2003
DOI: 10.1016/s0896-6273(02)01167-4
|View full text |Cite
|
Sign up to set email alerts
|

Pet-1 ETS Gene Plays a Critical Role in 5-HT Neuron Development and Is Required for Normal Anxiety-like and Aggressive Behavior

Abstract: The central serotonin (5-HT) neurotransmitter system is an important modulator of diverse physiological processes and behaviors; however, the transcriptional mechanisms controlling its development are largely unknown. The Pet-1 ETS factor is a precise marker of developing and adult 5-HT neurons and is expressed shortly before 5-HT appears in the hindbrain. Here we show that in mice lacking Pet-1, the majority of 5-HT neurons fail to differentiate. Remaining ones show deficient expression of genes required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
505
3
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(537 citation statements)
references
References 57 publications
24
505
3
5
Order By: Relevance
“…Chronic unpredictable stress further aggravates these traits. The impulsive and hyperaggressive behaviour of Tph2 2/2 mice resembles the increased defensiveness reported for Pet1 KO [17] and Tph2 R439H mutants [19]. Acute treatment with 5-HT 1A and 5-HT 1B receptor agonists (or 5-HT 2A/2C antagonists) via their inhibitory action on neurotransmission (pre-synaptically or post-synaptically) was reported to reduce aggressive behaviour, and it was suggested that low 5-HT levels in the brain are associated with maladaptive forms of excessive violence rather than with natural defensiveness [3].…”
Section: Tph2 In Personality Traits Of Negative Emotionality and In Dsupporting
confidence: 59%
“…Chronic unpredictable stress further aggravates these traits. The impulsive and hyperaggressive behaviour of Tph2 2/2 mice resembles the increased defensiveness reported for Pet1 KO [17] and Tph2 R439H mutants [19]. Acute treatment with 5-HT 1A and 5-HT 1B receptor agonists (or 5-HT 2A/2C antagonists) via their inhibitory action on neurotransmission (pre-synaptically or post-synaptically) was reported to reduce aggressive behaviour, and it was suggested that low 5-HT levels in the brain are associated with maladaptive forms of excessive violence rather than with natural defensiveness [3].…”
Section: Tph2 In Personality Traits Of Negative Emotionality and In Dsupporting
confidence: 59%
“…Deneris and colleagues have shown that the pheochromocytoma 12 ETS domain transcription factor-1, Pet-1, is essential for the generation of serotonin neurons, as evidenced by the ability of gene knockout of mouse Pet-1 to dramatically disrupt the differentiation of serotonin neurons during embryogenesis (Hendricks et al, 2003). Adult Pet-1 knockout mice exhibit a 70% loss of serotonin neurons, an 89% decrease in serotonin tissue content in cortex and hippocampus, and significant decrease in Tph2, serotonin transporter and Vmat2 mRNA expression in serotonin neurons that are extant (Hendricks et al, 2003).…”
Section: Serotonin Synthesismentioning
confidence: 99%
“…Adult Pet-1 knockout mice exhibit a 70% loss of serotonin neurons, an 89% decrease in serotonin tissue content in cortex and hippocampus, and significant decrease in Tph2, serotonin transporter and Vmat2 mRNA expression in serotonin neurons that are extant (Hendricks et al, 2003). Preliminary phenotypic analysis of these mice demonstrated an increase in anxiety-like behavior in some of the standard assays such as the novel open field and elevated zero-maze (for description and discussion of these tests, see Cryan and Holmes, 2005), as well as an increase in conspecific aggression (Hendricks et al, 2003). Pet-1 mice represent a powerful model for studying the stress-related consequences of genetically driven lifelong loss of brain serotonin (see also Lmx1b knockout mice (Zhao et al, 2006b)) and further data on these mice is eagerly anticipated.…”
Section: Serotonin Synthesismentioning
confidence: 99%
“…37 In contrast, deletion of Pet-1 results in partial loss of serotonin neurons (∼80%) in both the anterior and posterior cell groups. 38 A careful analysis of the surviving serotonergic neurons has shown that they selectively project to a small subset of areas, while other areas remain devoid of serotonergic innervation. 39 In the case of the DRN, the projection to the basolateral amygdala appeared to remain quantitatively intact after deletion of Pet-1, while the projection to the anterior cingulate cortex was nearly completely eliminated.…”
mentioning
confidence: 99%
“…This would explain the survival of a relatively constant fraction of neurons in the different serotonergic cell groups. 38 Identification of specific molecular markers for the Pet-1 deletionresistant cell population will be required to distinguish between these possibilities.…”
mentioning
confidence: 99%